Legal framework of central-local government administrative relationship in mainland Tanzania: A paradox of local autonomy - Mnyasenga, Thobias R.; Mushi, Eleuter G. (Uongozi Journal of Management and Development Dyanamics, 2024)
A research paper submitted to the Uongozi Journal of Management and Development Dynamics Vol. 26(1) (2015)